MODEL PENETUAN KAWASAN RESAPAN AIR UNTUK PERENCANAAN TATA RUANG BERWAWASAN LINGKUNGAN - Wibowo, Mardi (Jurnal Hidrosfir Indonesia, 2006)
Regional spatial planning is done for anticipate increasing and developpingsocial-economic activity. Generally, spatial planning tend to spatial valueand economic value, on the other hand environmental value is ignored. Forexample : in saptial planning is no space for conservation area for rechargearea. For determine (mapping) suitability a zone for recharge area needrequirements or a model for guidelines to determine recharge area. Generallyrequirements or parameter are used for mapping recharge area are materialpermeability, rain intensity, soil, slope and depth of groundwater surface.